Faktor Penyebab Penyalahgunaan dan Peredaran Narkotika di Wilayah Hukum Polresta Denpasar - I Gede Suariawan; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2022)
The development of drug abuse in Indonesia began around 1970, its users showed increasing symptoms, this is due to the development of the times and modern technology that has hit every aspect of life, modernization not only has a good impact but also has a bad impact, based on these developments, it is not It is undeniable that crime in Indonesia has increased. The purpose of this study is to analyze the factors causing the abuse and illicit trafficking of narcotics in the city of Denpasar and to discuss the prevention and control of narcotics abuse and illicit trafficking by the Denpasar Police. In studying the researchers used the type of empirical legal research using a sociological approach. The sources of data in this study include primary data obtained from interviews, secondary data including legislation, research results, legal expert opinions, legal papers contained in the mass media, legal books, legal journals and data tertiary which is supporting data that provides instructions and explanations for primary and secondary data. There are two data collection techniques, namely the library research method and the field research method. Efforts to overcome drug abuse include three efforts, namely preemptive efforts, which are early prevention efforts, preventive efforts, namely prevention efforts in the form of overcoming and repressive efforts, efforts made to eradicate legally, which are carried out by the Police, National Narcotics Agency, Government, Judges, and the community.